The Risk of Psychiatric Morbidity Following Teenage Induced Abortion and Childbirth – A Longitudinal Study From Finland - Jalanko E.; Leppälahti S.; Heikinheimo O.; Gissler M. (Elsevier USA, 2022)
Purpose: Teenage motherhood is associated with an increased risk of psychiatric morbidity. However, the long-term consequences of teenage induced abortion on psychiatric morbidity remain unknown. We, therefore, examined the association between adolescent pregnancy and psychiatric morbidity according to pregnancy outcome (induced abortion vs. childbirth) and age (<20 or <18 years) at the beginning of a pregnancy.
Methods: We used Finnish health care registers to evaluate the risk of psychiatric morbidity following teenage induced abortion (n = 6,520) or childbirth (n = 6,806) using Poisson regression analysis. The mean follow-up time was 26.4 years. Age-matched girls without a teenage pregnancy (n = 39,429) served as the reference group.
Results: The risk of psychiatric morbidity was higher in the teenage abortion group compared with those without a teenage pregnancy, but this risk increased only at 5 years postabortion. We found no difference in psychiatric morbidity between the teenage pregnancy groups aged <20 years (induced abortion vs. childbirth). However, women who underwent an abortion at <18 years of age instead of childbirth faced a lower risk of psychiatric morbidity, particularly during the first 5 years postabortion.
Conclusions: Pregnant adolescents faced an increased risk of psychiatric morbidity in adulthood regardless of the outcome (induced abortion or childbirth) of the pregnancy. Among girls aged <18 years, the risk of mental disorders was lower following abortion compared with childbirth. This finding should be acknowledged when counseling pregnant adolescents and organizing family planning services for teenagers.